Synthesis and Crystal Structure Analysis of Co(II) Complex with Terpyridine Ligand - Sun, Dan; Yuan, Xue-Mei; Yu, Xiao-Xiao; Xu, Hai-Jun (Asian Journal of Chemistry, 2015)
The Co(II) complex, [CoL2].[(ClO4)2]·[H2O] [L = 4'-(4-cyanophenyl)-2,2':6',2''-terpyridine], has been synthesized by the reaction of tridentate ligand L with Co(ClO4)2·6H2O and its structure was characterized by X-ray crystal structure analysis. The structure indicates that the complex belongs to monoclinic, space group Cc with a = 1.4018 (12) nm, b = 1.2223(10) nm, c = 2.520(2) nm, b = 100.676(9)º. V = 4.244 (6) nm3, Z = 4, Dc = 1.479 Mg m-3, μ = 0.598 mm-1, F(000) = 1932 and final R1 = 0.0683, wR2 = 0.1461. The result shows a Co(II) ion is six-coordinated by two tridentate 4'-(4-cyanophenyl)-2,2':6',2''-terpyridine ligand and forms a distorted octahedral-pyramidal geometry. The two benzene rings adjacent to the pyridines form dihedral angles of 31.76 (0.32) and 32.36 (0.33)° with the central pyridine ring systems, respectively. One of the ClO4 groups is disordered in two orientation with the site-occupancy factors 0.71 (2) and 0.29 (2). CCDC: 681080.